Soil pH Management for Optimum Commercial Fruit Production in Florida - Guodong Liu; Rao Mylavarapu; Ed Hanlon; Wei Chieh Lee (EDIS)
Soil pH is one of the most important soil chemical properties and affects nutrient bioavailability and microbial activity. The purpose of this article is to provide an overview for faculty, crop consultants, crop advisors, fruit growers, and students who are interested in fruit production. The crop response to soil pH varies due to crop genetic diversity. Soil pH determines nutrient bioavailability and hence fruit growth, yield, and quality. This 6-page fact sheet was written by Guodong Liu, Rao Mylavarapu, Ed Hanlon, and Wei Chieh Lee, and published by the UF Department of Horticultural Sciences, April 2014.